Zastosowanie konwertera adresów do zmniejszenia rozmiaru pamięci mikroprogramowanego układu sterującego ze współdzieleniem kodów - Kołopieńczyk, Małgorzata
The method of design of Compositional Microprogram Control Unit with Code Sharing is proposed. The proposed method is based on application of special address transformer to form an address of microinstruction on the base of its representation as a "code of operational linear chain, code of component" pair. The proposed method permits to decrease the size of control memory when compared to other methods of such control units design.
Keywords: jednostka sterująca; mikroprogramowany układ sterujący; sieć działań; konwerter adresów; logika programowalna; FPGA